Calcium hydrazinidoborane: Synthesis, characterization, and promises for hydrogen storage. (13th January 2020) - Ould-Amara, Salem; Yadav, Vibhav; Petit, Eddy; Maurin, Guillaume; Yot, Pascal G.; Demirci, Umit B.
Abstract: Viewing calcium hydrazinidoborane Ca(N2 H3 BH3 )2 (9.3 wt% H) as a potential hydrogen storage material, we long sought to synthesize it by solid-solid reaction of calcium hydride CaH2 and hydrazine borane N2 H4 BH3 . However, it was elusive because of unsuitable experimental conditions. In situ synchrotron thermodiffraction helped us to identify the key role played by the temperature in the formation of the new phase. From 45 °C, new diffraction peaks appear, and the DSC analysis shows an exothermic signal. Thermal activation is thus required to make solid-state CaH2 react with melted (liquid-state) N2 H4 BH3 . The XRD pattern can be indexed using a mixture of two phases: ( i ) unreacted CaH2 as a minor phase (29 wt%) and ( ii ) the hitherto elusive Ca(N2 H3 BH3 )2 (71 wt%). The as-formed Ca(N2 H3 BH3 )2 crystallizes in a monoclinic Ic (No. 9) unit cell where the intermolecular interactions form chains (layers) along the a axis, resulting in intra-chain and inter-chain Ca⋅⋅⋅Ca distances as short as 4.39 and 7.04 Å respectively. Beyond 90 °C, Ca(N2 H3 BH3 )2 decomposes, as evidenced by the diffraction peaks fading, an exothermic signal revealed by DSC, a weight loss (5.3 wt% at 200 °C) observed by TGA, and a gas release (H2, and some N2, NH3, N2 H4 ) monitored by MS. The as-formed thermolytic residue is amorphous and of complex polymeric composition. These results and the next challenges, are discussed herein. Graphical abstract: Image 1 Highlights: Hitherto-elusive calcium hydrazinidoborane Ca(N2 H3 BH3 )2 has been synthesized It forms above 45 °C, by solid-phase reaction of the precursors CaH2 and N2 H4 BH3 Ca(N2 H3 BH3 )2 crystallizes in a monoclinic Ic (No. 9) unit cell Ca(N2 H3 BH3 )2 carries 9.3 wt% H, and is thus a potential hydrogen storage material Ca(N2 H3 BH3 )2 starts to decompose at 90 °C, releasing mostly hydrogen